Statistics education research integrated with Islamic studies (A study of validity and practicality of textbook development) - Nufus, Hayatun; Fitraini, Depi (Jurnal Gantang, 2024)
This research is based on the need for a textbook of educational research statistics that is suitable for use, while its availability has not been met. Therefore, this research is a development study with ADDIE design (analysis, design, development, implementation, and evaluation), which aims to develop and produce an Islamic integrated educational research statistics textbook that meets valid and practical criteria. The data in this study were collected using questionnaire techniques and validity and practicality questionnaire instruments. Development is first carried out before these two instruments are used to ensure their feasibility. The data that has been obtained is analyzed using the Aiken index formula related to the calculation of validity and percentage related to practicality. The results of this study can be summarized in two conclusions. First, the Islamic integrated educational research statistics textbook is at the "very valid" validity level. The Aiken index score is 0.9215. Second, the Islamic integrated educational research statistics textbook based on mathematical communication skills is at the "practical" level of practicality. The numerical validity value is 77.66%. The implication of the results of this study is the production of a textbook that is suitable for use and tested for its effectiveness in learning educational research statistics.